Integrated wax valve for robust fluid control in an electrochemical fabric-based device. Issue 40 (3rd October 2019) - Downs, Corey; Nejely, Arianna; Fu, Elain
Abstract : We present a wax-based valve as a novel approach for fluid control in fabric-based microfluidic devices. Abstract : Although fabrics have great promise as substrates for use in wearable precision health applications, there has been relatively little attention focused on the development of control tools suitable for use in fabrics. Fluid control tools in fabric would enable the automation of multi-step sample processing on the device, reducing the need for off-chip sample handling. In this study, we describe the operation and characterization of a wax-based valving method with an integrated resistive heater in fabric for automated fluid delivery. The combination of wax-transfer-printed wax barrier and stencil-printed conductive ink heating element in fabric is a novel approach for achieving fluid control. We demonstrate robust valve operation and a rapid valve response time, and quantify the reproducibility of fluid flow through replicate valves. Further, we characterize wax redistribution in fabric using optical methods and scanning electron microscope imaging. Finally, we demonstrate valve utility in the context of on-device incubation in a fabric-based device for electrochemical glucose sensing. With a fabrication method that is compatible with a variety of substrates, this valving method has broad applicability.